2017
DOI: 10.1063/1.4996538
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrafast non-thermal laser excitation of gigahertz longitudinal and shear acoustic waves in spin-crossover molecular crystals [Fe(PMAzA)2(NCS)2]

Abstract: We report GHz longitudinal as well as shear acoustic phonons photoexcitation and photodetection using femtosecond laser pulses in a spin-crossover molecular crystal. From our experimental observation of time domain Brillouin scattering triggered by the photoexcitation of acoustic waves across the low-spin (LS) to high-spin (HS) thermal crossover, we reveal a link between molecular spin state and photoexcitation of coherent GHz acoustic phonons. In particular, we experimentally evidence a non-thermal pathway fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…Brillouin scattering requires usually transparent materials and the LS state does not fulfill this condition. More recently, ultrafast time‐domain Brillouin scattering experiments on single crystals of [Fe(PM‐AzA) 2 (NCS) 2 ] allowed for the photogeneration and photodetection of GHz acoustic phonons across the whole SCO temperature range . From Brillouin spectroscopy measurements, the longitudinal ( v l ) and transverse ( v t ) sound wave velocities are obtained, which can be linked to the isotropically averaged bulk modulus and shear modulus ( G ) through the material density ρ by vl2=B+4/3G/ρ and vt2=G/ρIn the case of iron complexes, which are the most frequent SCO compounds, 57 Fe Mössbauer spectroscopy was used at several instances to infer the lattice rigidity .…”
Section: Vibrational Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Brillouin scattering requires usually transparent materials and the LS state does not fulfill this condition. More recently, ultrafast time‐domain Brillouin scattering experiments on single crystals of [Fe(PM‐AzA) 2 (NCS) 2 ] allowed for the photogeneration and photodetection of GHz acoustic phonons across the whole SCO temperature range . From Brillouin spectroscopy measurements, the longitudinal ( v l ) and transverse ( v t ) sound wave velocities are obtained, which can be linked to the isotropically averaged bulk modulus and shear modulus ( G ) through the material density ρ by vl2=B+4/3G/ρ and vt2=G/ρIn the case of iron complexes, which are the most frequent SCO compounds, 57 Fe Mössbauer spectroscopy was used at several instances to infer the lattice rigidity .…”
Section: Vibrational Spectramentioning
confidence: 99%
“…Therefore, the chemical engineering of elastic properties appears as a difficult task, especially if one wish to enhance the lattice stiffness. An important parameter is the Poisson's ratio v , which can be determined in the isotropic approximation as follows: ν=3BY6BThis value was determined around ν=0.33--0.35 for three different SCO samples by Brillouin scattering and by combining HP‐XRD and NIS . It is interesting to note that for ν=0.33, the Young's and bulk moduli are equivalent.…”
Section: Vibrational Spectramentioning
confidence: 99%
“…It corresponds to the travel time of the volumic deformation through a microcrystal [Schick2014]. Thus, taking a sound velocity v ~ 4 * 10³ m.s -1 estimated from previous measurements on similar samples [Parpiiev2017] and L ~ 1.3 µm the average crystal dimension, the associated acoustic time scale is τ = L/v = 1.3*10 -6 / 4*10³ = 330 ps. Moreover, the initial photo-switching of 7% of the molecules causes the average volume jump of only 1.5 Å 3 (figure 1e), significantly smaller than the observed volume change of 19 Å at the maximum of volume expansion (figure 2c).…”
Section: Discussion On the Physical Picture Of Photo-induced Multistep Dynamicsmentioning
confidence: 99%
“…It has been also shown that during an ultrafast light-induced demagnetization process the shear acoustic phonons can exchange angular momentum with spins through the Einstein-de Haas effect [8,9] or sometimes called the Richardson effect [10,11]. Beyond these two examples, generating shear motion with light has received a great deal of attention in general, and several demonstrations of this phenomenon have been reported in different materials including multiferroic oxides, such as BiFeO 3 (BFO) [12][13][14], piezoelectric semiconductors GaN [15], GaAs [4], metals [4,5,16,17], or spin-crossover compounds [18] for citing a few. Despite this active and continuous effort, the underlying physics of the light-induced shear strain generation remains unclear since the quantitative measurement of the shear strain amplitude is lacking.…”
mentioning
confidence: 99%